Conférence: «Travail et santé au travail des femmes en contexte de pandémie» (2020)
La pandémie de COVID-19 a mis en lumière combien les femmes étaient en première ligne dans le système hospitalier et dans les soins aux personnes âgées au Québec. En d’autres mots : la pandémie a révélé l’importance de nombreux métiers mal rémunérés et souvent négligés, dont on se soucie peu, qui sont occupés à 80% par des femmes.
Keywords: 2000 à aujourd'hui; amériques; covid-19; femmes*; pandémie; personnes âgées; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques; travail; travail des femmes*

Le pouvoir de l’amour - EMMA (Emma, 2020)
Salut à toutes et tous, en ces temps confinés j’ai pensé vous mettre à disposition cette histoire inédite de mon tome 3 « La charge émotionnelle ». Je souhaite plein de …
Keywords: approches et analyses; bande-dessinée; care; charge mentale; discipline; discours dominant; femmes*; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; santé; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

LET'S GET YOU PREGNANT! : exploration critique de l'échec de la fécondation in vitro dans une pratique de l'installation - Barkun, Heidi (Université du Québec à Montréal, 2020)
Ce travail de recherche-création explore l’expérience de l’échec de la fécondation in vitro en employant une méthodologie d’autobiographie ancrée dans une critique institutionnelle féministe. Ayant suivi quatre ans de traitements de fertilité infructueux, j’incorpore ce vécu dans ma pratique émergente de l’installation contextuelle. Dans le chapitre I, je défends ma position en tant que sujet et objet de cet ouvrage. Le chapitre se termine avec une liste de termes employés dans ce mémoire. Le chapitre II considère les systèmes sociaux, médicaux et politiques qui gardent la maternité au premier plan de vie des femmes ; la fécondation in vitro y est examinée dans ce contexte élargi. La collection comme moyen de production artistique est analysée en lien avec l’œuvre Artéfacts provenant d’un rituel contemporain de fertilité (2016). Le chapitre III étudie la notion de l’échec et son impact sur les femmes en traitement de fertilité qui n’arrivent pas à devenir mères. Les pressions sociales et médicales qui amènent les femmes à utiliser la fécondation in vitro sont abordées en lien avec l’installation socially acceptable childlessness (2017) ; et la déhiérarchisation du site de l’œuvre est examinée en lien avec Échec quantifié (2017). Le chapitre IV analyse les politiques de l’espace et du son. Mon projet final LET’S GET YOU PREGNANT! explore le pouvoir de la parole en présentant le récit de 28 participantes, moi incluse, qui ont utilisé la fécondation in vitro sans succès et qui n’étaient pas mères au moment de l’entretien. L’élévation de la collection d’artéfacts de 16 des 28 participantes en statut d’œuvre d’art est étudiée. La possibilité de mener un éveil social par la voie de l’art conclut ce mémoire qui interroge l’industrie de la fécondation in vitro et repense la poursuite du succès à tout prix. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Installation – Fécondation in vitro – Échec – Corps féminin – Infertilité
Keywords: 2000 à aujourd'hui; IREF; arts visuels et médiatiques; discipline; mémoires/thèses; périodes historiques; recherche-création; ressource en ligne; santé; santé reproductive; thématiques

Kuei, je te salue: conversation sur le racisme - Béchard, Deni Ellis; Kanapé Fontaine, Natasha (Éditions Écosociété, 2020)
« En 2016, la poète lnnu Natasha Kanapé Fontaine et le romancier québéco-américain Deni Ellis Béchard entamaient une conversation sans tabou sur le racisme entre Autochtones et Allochtones. Comment cohabiter si notre histoire commune est empreinte de honte, de blessures et de colère? Comment faire réaliser aux Blancs le privilège invisible de la domination historique? Comment guérir les Autochtones des stigmates du génocide culturel? Ces questions traversent leurs échanges: Natasha raconte sa découverte des pensionnats autochtones, son obsession pour la crise d'Oka, la vie dans la communauté de Pessamit ; Deni parle du racisme ordinaire de son père, de la ségrégation envers les Afro-Américains, de son identité de Québécois aux États-Unis. Cinq ans plus tard, Deni et Natasha reprennent la plume pour poursuivre ce "rendez-vous de la parole qui s'ouvre". Renouant avec le ton intimiste et le foisonnement intellectuel de leur premier échange, ils abordent des sujets d'une brûlante actualité: mobilisation de Black Lives Matter après la mort de George Floyd, feux de forêt en Californie, campagne présidentielle sur fond de montée de l'intolérance; soulèvement des Wet'suwet'en et blocus ferroviaires, dénonciation de la politique de la reconnaissance du gouvernement Trudeau. Puis survient l'impensable: Joyce Echaquan, une Atikamekw de 37 ans, meurt sous les injures racistes de deux infirmières de l'hôpital de Joliette. Une vague d'indignation monte ...»–Quatrième de couverture.
Section: 203 pages ; 22 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; santé; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

Introduction: care aux Suds Quand le travail de care interroge les inégalités sociales - Borgeaud-Garciandía, Natacha; Guimarães, Nadya Araujo; Hirata, Helena (Revue internationale des études du développement, 2020)
Cet article introductif fait la lumière sur certains aspects de la production et de l’organisation du care dans des pays et régions dits « du Sud ». Partant d’une définition large du care, qui inclut ses dimensions sociales, politiques et éthiques, et des connaissances élaborées dans différents pays du Sud, trois thèmes centraux sont développés : le genre du care, les présences et carences de l’État, et les relations entre migrations et care. Ces thèmes sont sous-tendus par le rôle que jouent le care et sa distribution sociale sur les inégalités sociales et leur reproduction. L’article souligne à quel point nombre de travaux élaborés dans les Suds permettent d’interroger et d’enrichir la perspective du care et ses schémas explicatifs.
Keywords: approches et analyses; care; cours; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; thématiques; travail; éthique; éthique du care

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

Femmes invisibles: comment le manque de données sur les femmes dessine un monde fait pour les hommes - Criado-Perez, Caroline (First éditions, 2020)
Bienvenue dans un monde fait pour les hommes ... Imaginez un monde où votre téléphone portable vous glisse des mains parce qu'il est trop grand, où vous faites la queue des heures pour aller aux toilettes, où les médicaments que l'on vous prescrit peuvent être mauvais pour votre corps, et où un grand nombre de vos heures travaillées ne sont pas payées ... Si l'un de ces scénarios vous est familier, c'est sans doute que vous êtes une femme. Cela semble incroyable, mais c'est pourtant une réalité : la plupart des infrastructures et équipements que l'on utilise quotidiennement ont été pensés sans égard aux différences entre les sexes. Pourquoi? Parce que ce sont des hommes qui ont imaginé le monde dans lequel on vit, et qu'ils l'ont imaginé pour des hommes, à leur image. Ainsi, si les femmes ont souvent froid sur leur lieu de travail, c'est parce que la température des bureaux est basée sur le métabolisme d'un homme. Si elles sont plus susceptibles d'être gravement blessées lors d'accidents de la route, c'est parce que les tests de sécurité sont effectués sur des hommes d'1,77 m pesant 76 kilos. Enfin, si elles ont davantage de risques de mal réagir à certains médicaments, c'est, encore une fois, parce que les tests scientifiques sont effectués sur des hommes, sans prendre en compte les spécificités du corps féminin. Tout au long de cette enquête stupéfiante, Caroline Criado Perez montre que les femmes sont tout simplement absentes de la majorité des études statistiques, au détriment de leur santé, de leur sécurité, et parfois même de leur vie.
Keywords: approches et analyses; corps; domination masculine; histoire et politique; projet charge mentale; santé; sexisme; systèmes d'oppressions; thématiques; travail

Menstruation: Science and society - Critchley, Hilary O. D.; Babayev, Elnur; Bulun, Serdar E.; Clark, Sandy; Garcia-Grau, Iolanda; Gregersen, Peter K.; Kilcoyne, Aoife; Kim, Ji-Yong Julie; Lavender, Missy; Marsh, Erica E.; Matteson, Kristen A.; Maybin, Jacqueline A.; et al. (American Journal of Obstetrics and Gynecology, 2020)
Women's health concerns are generally underrepresented in basic and translational research, but reproductive health in particular has been hampered by a lack of understanding of basic uterine and menstrual physiology. Menstrual health is an integral part of overall health because between menarche and menopause, most women menstruate. Yet for tens of millions of women around the world, menstruation regularly and often catastrophically disrupts their physical, mental, and social well-being. Enhancing our understanding of the underlying phenomena involved in menstruation, abnormal uterine bleeding, and other menstruation-related disorders will move us closer to the goal of personalized care. Furthermore, a deeper mechanistic understanding of menstruation-a fast, scarless healing process in healthy individuals-will likely yield insights into a myriad of other diseases involving regulation of vascular function locally and systemically. We also recognize that many women now delay pregnancy and that there is an increasing desire for fertility and uterine preservation. In September 2018, the Gynecologic Health and Disease Branch of the Eunice Kennedy Shriver National Institute of Child Health and Human Development convened a 2-day meeting, "Menstruation: Science and Society" with an aim to "identify gaps and opportunities in menstruation science and to raise awareness of the need for more research in this field." Experts in fields ranging from the evolutionary role of menstruation to basic endometrial biology (including omic analysis of the endometrium, stem cells and tissue engineering of the endometrium, endometrial microbiome, and abnormal uterine bleeding and fibroids) and translational medicine (imaging and sampling modalities, patient-focused analysis of menstrual disorders including abnormal uterine bleeding, smart technologies or applications and mobile health platforms) to societal challenges in health literacy and dissemination frameworks across different economic and cultural landscapes shared current state-of-the-art and future vision, incorporating the patient voice at the launch of the meeting. Here, we provide an enhanced meeting report with extensive up-to-date (as of submission) context, capturing the spectrum from how the basic processes of menstruation commence in response to progesterone withdrawal, through the role of tissue-resident and circulating stem and progenitor cells in monthly regeneration-and current gaps in knowledge on how dysregulation leads to abnormal uterine bleeding and other menstruation-related disorders such as adenomyosis, endometriosis, and fibroids-to the clinical challenges in diagnostics, treatment, and patient and societal education. We conclude with an overview of how the global agenda concerning menstruation, and specifically menstrual health and hygiene, are gaining momentum, ranging from increasing investment in addressing menstruation-related barriers facing girls in schools in low- to middle-income countries to the more recent "menstrual equity" and "period poverty" movements spreading across high-income countries.
Number: 5
Keywords: amériques; corps; discipline; endométriose; gynécologie; menstruations; médecine; projet charge mentale; régions géographiques; santé; santé des femmes*; santé menstruelle; sciences; thématiques; états-unis

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques

Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Performers: _:n2788
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales

Précarité menstruelle Archives - RQASF (Campagne Rouge #LaVieEnRouge, 2020)
Le Réseau québécois d’action pour la santé des femmes se dédie à travers sa Campagne Rouge #LaVieEnRouge, qui durera 2 ans, à défaire les mythes et les tabous qui entourent les menstruations. Il s’agit d’une campagne participative: nous aurons besoin de vous tou.te.s pour parvenir à un changement global et positif concernant les perceptions et donc le vécu des menstruations… car nous sommes tou.te.s concerné.es! Précarité menstruelle S’engager contre la précarité menstruelle, c’est contribuer à une société plus équitable en favorisant l’accès pour toutes les personnes menstruées aux produits d’hygiène menstruelle. Découvrez la liste de nos partenaires collecteurs et distributeurs, et contactez-nous si vous souhaitez vous aussi vous engager: ensemble, tou.te.s solidaires contre la précarité menstruelle!
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; corps; menstruations; patriarcat; projet charge mentale; précarité menstruelle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles

Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*

Concilier famille et travail dans un horaire atypique ? - Souissi, Takwa (Gazette des femmes, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; charge mentale; conciliation famille-travail; famille; maternité; projet charge mentale; périodes historiques; québec; régions géographiques; santé; thématiques; travail; travail de la construction; travail domestique

Gender-based analysis using existing public health datasets - Tannenbaum, Cara (Canadian Journal of Public Health, 2020)
http://link.springer.com/10.17269/s41997-020-00302-9
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; histoire et politique; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé publique; thématiques

The Impact of COVID-19 on women - United Nations (United Nations Entity for Gender Equality and the Empowerment of Women (UN Women); United Nations Secretariat, 2020)
The year 2020, marking the twenty-fifth anniversary of the Beijing Platform for Action, was intended to be ground-breaking for gender equality. Instead, with the spread of the COVID-19 pandemic, even the limited gains made in the past decades are at risk of being rolled back. The pandemic is deepening pre-existing inequalities, exposing vulnerabilities in social, political and economic systems which are in turn amplifying the impacts of the pandemic. Across every sphere, from health to the economy, security to social protection, the impacts of COVID-19 are exacerbated for women and girls simply by virtue of their sex. This policy brief by the UN Secretary-General explores how women and girls’ lives are changing in the face of COVID-19, and outlines suggested priority measures to accompany both the immediate response and longer-term recovery efforts.
Keywords: 2000 à aujourd'hui; 2020-2029; covid-19; discipline; droit; droits des femmes*; droits humains; pandémie; projet charge mentale; périodes historiques; santé; science politique et droit; thématiques; violences; violences sexistes et sexuelles

Women worry about family, men about the economy: Gender differences in emotional responses to covid-19 - van der Vegt, Isabelle; Kleinberg, Bennett (Social Informatics, 2020)
Among the critical challenges around the COVID-19 pandemic is dealing with the potentially detrimental effects on people’s mental health. Designing appropriate interventions and identifying the concerns of those most at risk requires methods that can extract worries, concerns and emotional responses from text data. We examine gender differences and the effect of document length on worries about the ongoing COVID-19 situation. Our findings suggest that i) short texts do not offer as adequate insights into psychological processes as longer texts. We further find ii) marked gender differences in topics concerning emotional responses. Women worried more about their loved ones and severe health concerns while men were more occupied with effects on the economy and society. This paper adds to the understanding of general gender differences in language found elsewhere, and shows that the current unique circumstances likely amplified these effects. We close this paper with a call for more high-quality datasets due to the limitations of Tweet-sized data.
https://link.springer.com/10.1007/978-3-030-60975-7_29
Keywords: 2000 à aujourd'hui; 2010-2019; care; covid-19; discipline; europe; genre; langage; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; santé mentale; sciences humaines; sociologie; thématiques; émotions; étude quantitative

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Number: 5 Place: Birmingham Publisher: Emerald Group Publishing Limited
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

Adaptability to social distancing due to COVID-19 and its moderating effect on stress by gender - Zamarripa, Jorge; Delgado-Herrada, Maritza; Morquecho-Sánchez, Raquel; Baños, Raúl; de la Cruz-Ortega, Manuel; Duarte-Félix, Héctor (Salud mental, 2020)
The COVID-19 pandemic, originated in China, has affected millions of people worldwide, leading to various situations such as psychological disorders and diseases that affect people’s physical and mental health, and disrupt their quality of life. Objective. To analyze stress levels during social distancing due to COVID-19 by gender and to determine the moderating effect of adaptability to the situation. Method. The study is cross-sectional and quantitative, with a descriptive-correlational scope. The sample consisted of 1,173 Mexican subjects (522 males [44.5%] and 651 females [22.5%]) with an average age of 25.99 years (DT = 11.19; range = 12 - 77 years). Adaptability and perceived stress were measured, obtaining reliability from appropriate instruments. Results. The results indicated that the greater the number of weeks of social distancing, the higher the perceived level of stress. Also, the better people adapt to social distancing, the less stress occurs. Women were observed to have higher levels of stress compared to men. Discussion and conclusion. The findings highlight the importance of adaptability to the stressful situation of the pandemic, because the effect of severe stress on women largely disappears when there is a high level of adaptability to the event.
Number: 6 https://www.scielo.org.mx/scielo.php?script=sci_arttext&pid=S0185-33252020000600273
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; covid-19; mexique; périodes historiques; ressource en ligne; régions géographiques; santé; santé mentale; stress; thématiques; étude quantitative

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis